THE COMPARATIVE STUDY ANALYSIS LOGICAL FILES RECOVERY AND LOW LEVEL FILES RECOVERY USING DIGITAL FORENSIC METHODS - Rahmat Hidayat; Marza Ihsan Marzuki; Yuliarman Saragih; Ibrahim Ibrahim; Edmund Ucok Armin; Safrian Andromeda; Imam Budi Santoso; Suroyo Suroyo (Department of Computer Engineering, Universitas Wiralodra, 2022)
The development of application and network technology is currently so rapid. This technology is widely used as a solution to overcome data inspection problems in the field of Digital Forensics. The importance of Digital Forensics as evidence, especially on computers and mobile devices, is increasing, along with the rapid use of these mobile devices in daily communication. Data and files on computers and smartphones can be deleted intentionally or unintentionally. To recover the data, it is necessary to have Files Recovery. Furthermore, Logical Files Recovery can be made through password encryption, obtained through hack/attack password applications such as Password or even hacked with the